Genetic diversity and pathogenicity of sorghum-associated Fusarium species - Bushula, Vuyiswa Sylvia (Kansas State University, 2017)
Understanding the genetic structure of fungal pathogens enables the prediction of evolutionary forces that drive pathogen evolution, which assists informed decision-making regarding disease management. The genetic structure of Fusarium thapsinum and F. andiyazi, two important pathogens that cause grain mold and stalk rot of sorghum (Sorghum bicolor), are little understood. The genetic structure and pathogenicity of a F. thapsinum population from sorghum in Kansas were evaluated with amplified fragment length polymorphisms (AFLPs), vegetative compatibility groups (VCGs), sexual cross-fertility, and seedling pathogenicity. Two sympatric populations and a genetically intermediate "hybrid" group were identified in Kansas. Seedling pathogenicity of strains ranged from non-pathogenic to pathogenic, which may be partially attributable to genetic variability in the F. thapsinum populations. Genetic relatedness between populations of F. thapsinum from sorghum in Kansas, Australia, Thailand, and three African countries (Cameroon, Mali, and Uganda) were evaluated with AFLP markers and sexual crosses. Genetic diversity was high in all locations, but female fertility is very low. These results are consistent with the hypothesis that both sexual and asexual modes of reproduction are important components of the life cycle of F. thapsinum in these populations. More strains from Kansas and Africa were available for analysis than from Australia and Thailand, so the Kansas and Africa populations dominated the genetic structure observed. The two smaller populations from Australia and Thailand were more closely related to the Kansas population than they were to the African population. The three non-African populations contained information from the African population and from other, as yet unidentified, source population(s). Identifying the population(s) from which this genetic diversity originated is an important unanswered question. Stalk rot of sorghum was evaluated by inoculating stalk rot sensitive and stalk rot resistant sorghum lines with six genetically diverse F. thapsinum strains from Kansas under field and greenhouse conditions. One susceptible line (Tx7000) and two resistant lines (SC599 and BTx399) were evaluated in the field but only Tx7000 and SC599 were evaluated in the greenhouse. Disease severity was measured by major lesion length and the number of nodes crossed by the lesion. There were differences in aggressiveness amongst the F. thapsinum strains in both the greenhouse and field evaluations. This study provides the first evidence for differences in stalk rot aggressiveness amongst F. thapsinum strains and highlights the importance of challenging germplasm with well-characterized strains that represent the genetic spectrum of the entire population. The genetic diversity within F. andiyazi populations and some closely related strains was evaluated with AFLP markers. Phylogenetic and STRUCTURE analyses of the AFLP markers grouped the 81 F. andiyazi strains into three distinct clusters. The clusters were not based on the geographic origin of the strains. These results indicate the presence of at least one and possibly two undescribed sister taxa of F. andiyazi. More work is needed to further characterize these sister species of F. andiyazi and to understand their role in sorghum pathogenicity. There is genetic variation in global populations of F. thapsinum and the observed variation could be associated with variation in both seedling and adult plant pathogenicity. The study of F. andiyazi populations validated the need to properly identify and characterize Fusarium spp. associated with sorghum from different regions of the world.
Keywords: Genetic diversity; Pathogenicity; Sorghum bicolor; Fusarium